Photoelectrons and solar ionizing radiation at Mars: Predictions versus MAVEN observations. Issue 9 (1st September 2016) - Peterson, W. K.; Thiemann, E. M. B; Eparvier, Francis G.; Andersson, Laila; Fowler, C. M.; Larson, Davin; Mitchell, Dave; Mazelle, Christian; Fontenla, Juan; Evans, J. Scott; Xu, Shaosui; Liemohn, Mike; et al.
Abstract: Understanding the evolution of the Martian atmosphere requires knowledge of processes transforming solar irradiance into thermal energy well enough to model them accurately. Here we compare Martian photoelectron energy spectra measured at periapsis by Mars Atmosphere and Volatile Evolution MissioN (MAVEN) with calculations made using three photoelectron production codes and three solar irradiance models as well as modeled and measured CO2 densities. We restricted our comparisons to regions where the contribution from solar wind electrons and ions were negligible. The two intervals examined on 19 October 2014 have different observed incident solar irradiance spectra. In spite of the differences in photoionization cross sections and irradiance spectra used, we find the agreement between models to be within the combined uncertainties associated with the observations from the MAVEN neutral density, electron flux, and solar irradiance instruments. Key Points: We report Martian photoelectron energy spectra obtained on 19 October 2014 We compare model energy spectra using observed EUV and XUV irradiances and in situ neutral densities We find agreement between models and observations within experimental uncertainties